Cytokine production by endothelial cells infected with human T cell lymphotropic virus type I. Issue 9 (September 1996) - Takashima, H; Eguchi, K; Kawakami, A; Kawabe, Y; Migita, K; Sakai, M; Origuchi, T; Nagataki, S
Abstract : OBJECTIVE: To investigate the ability of human T cell lymphotropic virus type I (HTLV-I) to infect endothelial cells and induce cytokine production by these cells. METHODS: Human umbilical vein endothelial cells (HUVEC) were cocultured with HTLV-I infected T cell line (MT-2 cells) or uninfected T cell line (CEM cells). RESULTS: Following coculture with MT-2 cells, endothelial cells expressed HTLV-I specific core antigens. Endothelial cells cocultured with MT-2 cells produced significant amounts of several cytokines, including interleukin (IL)-1 alpha, IL-6, granulocyte colony stimulating factor (G-CSF), and granulocyte/macrophage colony stimulating factor (GM-CSF), compared with endothelial cells cocultured with CEM cells. Coculturing of endothelial cells with MT-2 and CEM cells failed to produce detectable amounts of IL-1 beta and tumour necrosis factor alpha (TNF-alpha). The production of cytokines by endothelial cells cocultured with MT-2 cells was more persistent than that by endothelial cells cocultured with CEM cells after several passages. Furthermore, the production was blocked by cocultivation of endothelial cells and MT-2 cells using the Millicell system. Finally, after cocultivation of endothelial cells and MT-2 cells, endothelial cells positive for HTLV-I antigen were stained by anti-GM-CSF antibody. CONCLUSIONS: HTLV-I can infect endothelial cells, resulting in their active production of several cytokines, such as IL-1 alpha, IL-6, G-CSF, and GM-CSF. These findings strongly suggest that the excess production of these cytokines by HTLV-I infected endothelial cells may be involved in the pathogenesis of HTLV-I associated inflammatory diseases.